Control of international capital movements - Otto Pfleiderer (Intereconomics, 1972)
As the periodic surges of international capital movements undermine stability, the question arises at what rate of priority the principle of unhampered international capital movements should be treated, and whether there are potential alternatives to replace this principle.
Keywords: 330; Monetary Policy